Administrative Procedure as an Instrument of Public Administration - Mykhailo Shtyka (Bulletin of the Academy of Labor, Social Relations and Tourism. Series: Economics, Psychology and Management, 2026)
The article examines the managerial dimension of administrative procedure as regulated by the Law of Ukraine "On Administrative Procedure". It is argued that administrative procedure, although traditionally perceived primarily as a procedural guarantee of individual rights and legitimate interests, simultaneously functions as a formalised model of managerial decision-making by a public administration entity and as an instrument of internal administrative management. The paper analyses the functional manifestations of the managerial character of administrative procedure, namely the rationalisation of decision-making, the regulation of discretionary powers, the guarantee of transparency and accountability, the organisational structuring of the activity of public authorities, and the algorithmisation and standardisation of procedural actions under the conditions of digitalisation of public administration. Based on a systemic and formal-logical analysis of normative material and scholarly sources, the author proposes an understanding of administrative procedure as a managerial cycle comprising the stages of planning, organisation, decision-making and control. The scientific novelty lies in the proposed correlation between the stages of the administrative procedure and their managerial purpose. In particular, the formulation of the managerial problem is carried out at the first stage of the administrative procedure - the opening of proceedings; the provision of the resource and information base for the decision is ensured at the second stage of the procedure - the study of the circumstances of the case and the collection of evidence; the third stage of the administrative procedure, the adoption of an administrative act, is associated with the exercise of the discretion of the authority; and the provision of feedback is implemented through appeal, review and execution of the act. Аt the same time a managerial reading of administrative procedure does not contradict but rather complements its procedural-guarantee nature, thereby broadening the theoretical toolkit of public administration for assessing the institutional capacity of public authorities. The findings may be applied to improve the internal regulations of administrative bodies, to develop standards of electronic administration, and to build the managerial competencies of civil servants.